STRUKTUR DAN KOMPOSISI TUMBUHAN INVASIF DI HUTAN LINDUNG GAMBUT SUNGAI BULUH KABUPATEN TANJUNG JABUNG TIMUR - Ihsan, Mahya; Suprayogi, Dawam; Prima Nugraha, Anggit (Universitas Jambi, 2022)
The Study of structure and compotition of invasive species in protected peat forest area of ​​the Sungai Buluh, Tanjung Jabung Timur was conducted from April to September 2020. This research was conducted in open space area. Data were collected with systematic sampling method in 2 x 2 m plot in tree long transects 500 m. Every transect has 5 plots with the same distance of 100 m, so that the total plots are 25 plots. The data obtained were analyzed to determine the importance value indeks of plant species, diversity indeks and Eveness index of plants in the location. Based on the identification results, were found 31 invasive spesies in Protected Peat Forest Sungai Buluh. Cynodon dactylon was found high Important Value Index 28.60%. Diversity index was found 2,65 and the value of the evenness index 0,77 in research location.